Ordered SnO2 nanotube arrays of tuneable geometry as a lithium ion battery material with high longevity - Zhuo, Ying; Tymek, Sarah; Sun, Hong; Barr, Maissa; Santinacci, Lionel; Bachmann, Julien (Nanoscale Advances, 2020)
Ordered arrays of straight, parallel SnO2 nanotubes are prepared by atomic layer deposition (ALD) on inert 'anodic' aluminum oxide porous membranes serving as templates. Various thicknesses of the SnO2 tube walls and various tube lengths are characterized in terms of morphology by scanning electron microscopy (SEM), chemical identity by X-ray photoelectron spectroscopy (XPS) and phase composition by X-ray diffraction (XRD). Their performance as negative electrode ('anode') materials for lithium-ion batteries (LIBs) is quantified at different charge and discharge rates in the absence of additives. We find distinct trends and optima for the dependence of initial capacity and long-term stability on the geometric parameters of the nanotube materials. A sample featuring SnO2 tubes of 30 µm length and 10 nm wall thickness achieves after 780 cycles a coulombic efficiency of >99% and a specific capacity of 671 mA h g-1. This value represents 92% of the first-cycle capacity and 86% of the theoretical value.
CRIS-Team Scopus Importer:2020-04-28